Target Plant Concept (TPC) : A Holistic Framework for Seedling Quality within a Forest Restoration Programme - Mugunthan, Perumal; Mohd Effendi, Wasli (Institut EkoSains Borneo, Universiti Putra Malaysia Bintulu Sarawak Campus, 2023)
The quality of seedlings is essential to any successful forest restoration programme. The physical and genetic characteristics of seedlings are referred to as seedling quality. Physical quality refers to the physical condition of seedlings as they grow in the nursery, whereas genetic quality refers to the genetic characteristics of the germplasm source [1]. Although good nursery practices can improve seedling’s physical quality, there is no quick fix to enhance seedling genetic quality. The concept of seedling quality has evolved over the past century to the point where plant attributes are used to improve seedling nursery culture and forecast seedling survival and growth after outplanting [2].